Effect of Kaolinite on the Mechanical Properties, Thermal Properties, Flammability and Water Absorption Percentage of Poly (Vinyl Chloride) Composite - Abdul majeed, Basma A.; sabar, Dhilal amer (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
PVC/Kaolinite composites were prepared by the melt intercalation method. Mechanical properties, thermal properties, flammability and water absorption percentage of prepared samples were tested. Mechanical characteristic such as tensile strength, elongation at break; hardness and impact strength (charpy type) were measured for all samples. It was found that the tensile strength and elongation at break of PVC composites decreased with increasing kaolinite loading. Also, the hardness of the composites increases with increase in filler content .The impact strength of the composites at the beginning increases at lower kaolinite loadings is due to the lack of kaolin adhesion to the matrix. However, at higher kaolin loadings. This severe agglomeration of the filler due to its high surface energy creates many crack-initiation and stress-concentration sites, which are sensitive to impact stresses and cause detrimental effects on the impact properties of the composite. There is a general increase in absorption rate with increase in kaolin content. Thermal properties of PVC /kaolinite composites were characterized using Differential Scanning Calorimetry (DSC) and thermal conductivity analyzer. The results showed Tg shifted toward higher temperature for kaolinite composites compared to neat PVC .Also, thermal conductivity measurement value and effusivity increased with increasing filler loading .Heat capacity decreased with increasing filler content. The higher the filler content the higher burning time, the lower rate of burning and the lower height of the flame which are evident at 12wt. % for kaolinite.